Competence of Cryopreserved Oocytes After Enucleation and the First Polar Body Transfer to Ooplasm - Buderatska, Natalya O.; Ilyin, Igor Ye.; Lavrynenko, Sergii V. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(2): 168